Pengaruh Promotion Mix Terhadap Keputusan Pembelian Sepeda Motor Suzuki Di Kota Makassar (studi kasus pada PT.Sinar Galesong Mandiri) - Malik, A. Jihan Rahmadani; Ramli, Anwar; Musa, Muhammad Ichwan; Haeruddin, Muh. Ilham Wardhana; Hasdiansa, Ilma Wulansari (Faculty of Islamic Economics and Business, Madura Islamic State University, 2024)
This research is a quantitative study that aims to determine the effect of promotion mix on purchasing decisions for suzuki motorbikes in Makassar city. The population in this study were all consumers who had transacted at PT Sinar Galesong Mandiri for the last three years with a sample of 54 respondents. The data collection technique used is a questionnaire. The analysis technique used is multiple linear regression using Statistical Product and Service Solution (SPSS 20). The results of this study indicate that simultaneously the Promotion Mix variables (advertising, personal selling, sales promotion, publicity) have a significant effect on purchasing decisions. Partially, it shows that personal selling and sales promotion variables have a positive and significant effect on purchasing decisions for suzuki motorbikes, while advertising and publicity have no positive and insignificant effect on purchasing decisions